Letter: hepatitis B reactivation in patients with chronic hepatitis C during direct‐acting antiviral therapy—authors' reply. Issue 12 (15th May 2017) - Londoño, M.‐C.; Carrión, J. A.; Forns, X.
Abstract : Linked Content This article should be linked to Londoño et al and Huang et al papers. To view these articles visithttps://doi.org/10.1111/apt.13985 andhttps://doi.org/10.1111/apt.14080 .